Trend dalam corak hujan tahunan ekstrim di Semenanjung Malaysia dari 1975-2004 - Wan Zawiah Wan Zin,; Abdul Aziz Jemain , (Penerbit ukm, 2008)

(untitled)
Trends in annual maximum rainfall in Peninsular Malaysia have been analysed using daily rainfall records at 50 stations for 30 years. In this study, annual maximum rainfall is defined as the maximum daily rainfall amount recorded in a particular year. Both North-East Monsoon and South-West Monsoon are separated to identify their effect on the extreme rainfall. Rank von Neumann correlation test was performed to detect any correlation between years and followed by Kendall test to detect any significant trend. The magnitude of trends for stations with significant trend was derived from linear regression and computed to get the change value for a century. The results show that only 10% of the stations under study experience either significant increasing or decreasing trends in annual maximum rainfall. Apart from that, the pattern of extreme rainfall received is influenced by respective stations’ location